Prevalence Of Low Back Pain In Working Nurses In University Hospitals: An Epidemiological Study - Eidah Muflih Alrashedi , Danah abdualaziz alshuiee , Mashael Mishal Alhgeli , Albandari ali Almutairi , Saud obaid alanazi , Nourh khatim Almutairi , mohammed rashed aldossari , Norah Muqbil M Almutairi; Asma Mohammed Moafa , Fahida Mohammed alanzi , maha abd alanazi , Nadia Dafer Majdua Alsharei , Dalal Ayed Alotaibi , Bashayer saleam alrefai , Mona Zayed Alrashidi (Migration Letters, 2022)
Background: Nursing is associated with a heightened risk of low back pain (LBP) due to the combined physical and mental demands of the profession. Objective: This study aimed to determine the prevalence of chronic LBP and identify associated risk factors among nursing personnel at University Hospitals. Methods: This quantitative, retrospective, analytical, cross-sectional study involved 150 female nurses currently employed at University Hospitals. Par[1]ticipants completed a self-administered Oswestry Low Back Disability Questionnaire, and data on risk factors (age, height, weight, BMI, marital status, parity) and working conditions (employment duration, weekly working hours, job demands, absenteeism) were collected. Results: LBP was prevalent in 79.3% of the nurses, with the highest prevalence in ICU nurses (95.0%) and the lowest in outpatient clinic nurses (64.0%). There was a significant association between LBP and BMI (P < 0.001). Lifting heavy loads, twisting, prolonged standing, sitting, walking long distances, and forward bending were identified as significant contributors to LBP incidence. Conclusion: The high prevalence of LBP among nurses underscores the need for multidisciplinary interventions to mitigate its impact and associated costs.